Study of the impact of ash fallout from the Icelandic volcano Eyjafjöll (2010) on vegetation using MODIS data - Ifkirne, Mohammed; Beri, Quentin; Schaefer, Alex; Pham, Quoc Bao; Acharki, Siham; Farah, Abdelouahed (Natural hazards (Dordrecht), 2022)
Volcanic ash fallout is a recurrent environmental disturbance of flora ash deposits from the Icelandic volcano Eyjafjöll (2010) over large areas are responsible for several impacts on ecological processes, agricultural production, and human health in Western Europe. This study assessed the ash fall effects from the subject volcano on the surrounding flora as well as vegetative recovery at two different sites (Scotland and southern Sweden). For this purpose, we analyzed Normalized Difference Vegetation Index (NDVI), Leaf Area Index (LAI), and Fraction of Photosynthetically Active Radiation absorbed by Plants (FPAR) data provided by the Moderate Resolution Imaging Spectroradiometer (MODIS). The cited biophysical variables were most strongly influenced by ash cloud fallout, with the lowest maxima recorded for both sites during the 2010 eruption year. To confirm this impact, a statistical study with climate indicators was performed. The results showed a significant correlation between LAI and precipitation ( R 2 = 0.63, p-value = 0.0022) at site 1 (Scotland), while a weak non-significant correlation ( R 2 = 0.2248, p-value > 0.5) was observed at site 2. However, climatic data from both sites showed low correlations ( R 2 < 50%) with NDVI vegetation indicator. Despite the heavy rainfall and heat recorded during this period, our statistical results show us that ash cloud fallout affects vegetative development.